Netter's clinical anatomy - Hansen, John T.; Netter, Frank H. (Frank Henry) 1906-1991 (Elsevier, 2019)
"Focus on the clinically relevant aspects of anatomy and bridge normal anatomy to common clinical conditions with Netter's Clinical Anatomy, 4th Edition. This easy-to-read, visually stunning text features nearly 600 superb Netter-style illustrations that provide essential descriptions of anatomy, embryology, and pathology to help you understand their clinical relevance. Authored by John Hansen, PhD, an Honored Member of the American Association of Clinical Anatomists, this book is an ideal anatomy reference for students who want to make the most of their study time or need a concise review of clinical anatomy."